Impact of Online Preparation Modules on Students’ Engagement and Interactions in Face-to-Face Fluid Mechanics Laboratories - Cisonni, Julien; Lucey, Tony; Sarukkalige, Ranjan; Lal, Sulakshana (2023)
The transformation of laboratory activities to better embed the development of essential personal attributes and the attainment of specific learning outcomes in the engineering curriculum has been supported by the integration of online preparation modules. Beyond the widely demonstrated effectiveness of multimedia pre-laboratory activities in strengthening students’ engagement and preparedness for the execution of experimental tasks, this study also focuses on the effect of these online modules on student-student and student-instructor interactions in face-to-face fluid mechanics laboratories. Survey data show that students with a mid-level of academic performance were more likely to adopt the new resources but that most students perceived them as a valuable complement to, or replacement for, the traditional instruction sheet. While students’ self-assurance in conducting the laboratory tasks and appreciation of the instructor’s support appear unaffected by the completion of the modules, observations suggest these modules can strengthen students’ autonomy and engagement within their group during the conduct of the laboratory activities. Indeed, the introduction of the modules appears to facilitate a transition of the instructor’s role from directing the laboratory to guiding students in peer-learning.